EDUKASI PHBS BERBASIS LEAFLET MENINGKATKAN PENGETAHUAN SISWA SMKS KESEHATAN DARUSSALAM LHOKSEUMAWE - Ulfa, Meutia; Siswanto Pabidang; Fatya Nurul Hanifa (LPPM Akademi Manajemen Administrasi Yogyakarta, 2026)
This community service activity addressed the suboptimal knowledge and implementation of Clean and Healthy Living Behavior (Perilaku Hidup Bersih dan Sehat/PHBS) among adolescents in the school setting. The activity aimed to improve students’ knowledge of PHBS through structured health education using an educational leaflet entitled “PHBS di Sekolah: Sehat Itu Keren!”. The method employed was a participatory face-to-face health education approach involving interactive lectures, discussions, question-and-answer sessions, and practical demonstrations. The activity was conducted on January 14, 2026, at SMKS Kesehatan Darussalam, Lhokseumawe City, involving 28 students. Evaluation was carried out using pre-test and post-test questionnaires. The results showed a significant improvement in students’ knowledge after the intervention. The proportion of participants with good knowledge increased from 32.1% before education to 75.0% after education, while the mean knowledge score increased from 68.81% to 87.62%. These findings indicate that PHBS education using leaflet media is effective in enhancing adolescents’ knowledge and can serve as a strategic approach to strengthening sustainable healthy behavior practices in the school.